Distribution of Jurassic nannofossils at DSDP Leg 79 Holes - George E Wiegand (PANGAEA, 1984)
Sites 544, 545, and 547, drilled on DSDP Leg 79, recovered Jurassic calcareous nannofossils. Lower Jurassic (Sinemurian - lower Pliensbachian) nannofossils are found in Hole 547B; these are the oldest yet recovered by deep sea drilling. Three other Jurassic intervals are delineated by nannofossil biostratigraphy: the Lower-Middle Jurassic in Hole 547B; the Lower-Middle Jurassic in Hole 545; and the Upper Jurassic in Hole 547B. Low species diversity makes age determinations difficult for these portions of the Jurassic. Two new genera, Calcivascularis and Orthogonoides, have been described from these Lower Jurassic sediments.
Supplement to: Wiegand, GE (1984): Jurassic nannofossils from the Northwest African Margin, Deep Sea Drilling Project Leg 79. In: Hinz, K; Winterer, EL; et al. (eds.), Initial Reports of the Deep Sea Drilling Project, Washington (U.S. Govt. Printing Office), 79, 657-670, https://doi.org/10.2973/dsdp.proc.79.125.1984